(untitled) (Applied Biological Research, 2023)
The present field experiment was aimed to assess the effect of planting geometry and plant growth regulators on the growth and flowering of chrysanthemum (Dendranthema grandiflora). The study was carried out in the experimental field of Dau Kalyan Singh College of Agriculture & Research Station, Bhatapara (India) in the Department of Floriculture and Landscape Architecture, IGKV, Raipur (C.G.) during the year 2018-2019 in rabi season. The results revealed that planting chrysanthemum at 30 x 30 cm spacing increased plant height while the plant spacing of 30 x 45 cm enhanced the number of leaves plant-1, number of branches plant-1, plant spread, number of flowers plant-1, flower size and single flower weight. Among different growth regulators, maximum plant height, leaves plant-1, branches plant-1, plant spread, flowers plant-1, flower size and single flower weight was observed in the plants sprayed with gibberellic acid (GA3) @ 200 ppm. The interaction of 30 x 30 cm spacing and GA3 application @ 200 ppm gave taller plants while the treatment-combination of 30 x 45 cm spacing and GA3 use @ 200 ppm had highest number of leaves and branches plant-1 and maximum plant spread.